Comparison evaluation between gene Xpert Mtb/Rif and multiplex PCR for rapid diagnosis of mycobacterium tuberculosis - Saira Salim; Wajid Hussain; Gohar Zaman; Umer Khurshid; Luqman Satti (Journal of the Pakistan Medical Association, 2020)
Objective: To evaluate Gene Xpert MTB/RIF and Multiplex PCRfor detection of Mycobacterium tuberculosis and Rifampicin resistance comparing with gold standard MGIT 960. It was cross sectional validation study. Methods: This study had been carried out at Department of Microbiology Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan from March 2018 to October 2018.MGIT 960 culture system MTB positive Rifampicin (RIF) resistant and RIF susceptible (negative control) samples were taken. Gene Xpert MTB / RIF assay and Multiplex PCR were applied simultaneously and compared with gold standard MGIT 960. Results: Out of 192 samples evaluated, 84(44%) were culture positive RIF resistant and 108(56%) were culture positive RIF susceptible as negative control. Out of total culture positive RIF resistant, all 84 were found positive for MTB by Gene Xpert MTB /RIF assay and Multiplex PCR method. Gene Xpert MTB/RIF assay detected all 84 RIF culture resistant samples for Rif resistance. Multiplex PCR detected only 44 RIF culture resistant, while remaining 40 did not showed resistance to rpoB gene codon 531 region. Sensitivity, Specificity, PPV and NPV of Gene Xpert MTB/RIF were 100% each respectively. Sensitivity, Specificity, PPV and NPV of Multiplex PCR for detection of RIF resistance were 52%, 100%, 100%, 72% respectively. Conclusion: Molecular detection of MTB and RIF resistant by Gene Xpert MTB/ RIF and Multiplex PCR simultaneously is rapid and cost effective method. Both methods can help clinician to initiate early empirical therapy to patient in resource limited region. Keywords: RIF, Gene Xpert MTB/ RIF, Multiplex PCR.